Deforestation in Malaysia: An economic perspective / Azniza Ahmad Zaini - Ahmad Zaini, Azniza (2005)
Tropical forests play significant role in the conservation of biodiversity and known as one of the most complex ecosystems in the world. Unfortunately, at the end of the twentieth century, it is estimated that the world has lost approximately 40 per cent of the original forest area of 6,000 million hectares over the last 8,000 years and most of the loss of forest area is a direct consequence of human interference in the 20th century. Thus, the scope of this report is to discuss deforestation in Malaysia, particularly in Sarawak. One of the economic phenomena that may have contributed to the problem such as logging will be discussed. In addition, the efficiency and effectiveness of the policies that have been undertaken by the government to solve the problems such as concessions, and also the impediments which may be encountered in applying those polices are also provided in this paper.